Rencana Pendapatan Belanja Pendidikan - Ano Suherlan (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This article was written in order to construct the concept of an education expenditure income plan. The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results of this article is an activity or project that contains details of expenses for a certain period so that existing institutions can be used optimally to support the achievement of education.